Questão social e educação do campo na Amazônia: análise da realidade institucional nas escolas municipais da comunidade Vila Amazônia/Parintins/Amazonas - Babosa, Elouíze da Silva (Brasil, 2024)
The purpose of this study is to know the institutional reality of the municipal schools in the community of Vila Amazônia/Parintins-AM. To this end, it is initially intended to characterize rural education in the Amazon in order to situate the volume of attention received from the public power in the face of the demands of the school community. In the same way, it is proposed to identify the education scenarios in the municipality in question. Also in this bias, analyze the role of the public power in the face of the demands arising from educational institutions, located in Vila Amazonia. In the municipality of Parintins, as well as in other regions of the country, education undergoes external modifications, whether due to political, economic, religious or cultural structures. As a result, the study of rural education is primarily delimited, which experiences processes of precariousness in the pedagogical and structural system, especially schools regarding the transfer of funds, the conditions of assistance and investment in communities in general. In the Amazon, education in the countryside is still popularly referred to as rural, especially when related to traditional communities. These schools have precarious structural and pedagogical conditions, such as the serial education system, adopted in numerous regions of the Amazon. Such conditions are challenging for teachers and students and directly impact the quality of teaching. This research proposes an analysis of the reality of the municipal schools in the community of Vila Amazônia, focusing on the structural conditions of the Tsukasa Educational Center, through observation and exploratory research carried out in this community. Knowing these realities and particularities express the commitment of the research with regard to analyzing and seeking answers to the attenuating differences between urban schools and rural schools. It is therefore necessary to add the results obtained in the process of documentary research, which showed that the financial transfers available to educational institutions in the field were insufficient. The results point to low percentages available of total transfers between the years 2016 and 2023. In 2016, according to the details of Education expenses, spending on the construction, renovation and expansion of rural schools totaled 2% of all resources made available for education as a whole. Another problem observed, based on the reports made during the internship period at SEMED, is the on-site monitoring of the Department of Education with the schools in the community of Vila Amazônia due to the lack of resources. Because of this, it is intended to signal the problems experienced in this context, but also to contribute to the category of social service, so that actions/projects can be thought of and elaborated that aim to serve the communities with regard to rural education, consequently improving the conditions of action of local teachers.